Jaminan Kehilangan Pekerjaan terhadap Pekerja/Buruh Akibat Pemutusan Hubungan Kerja Sebagai Upaya Mewujudkan Keadilan - Eddy, Sagoro; Saputro, Bambang; Tinambunan, Wahyu Donri (Wajah Hukum, 2025)
Post the enactment of the Job Creation Law, the Government has established Government Regulation Number 37 of 2021 concerning the Implementation of the Unemployment Insurance Program, which is one of the government's policies related to additional employment social security guarantees that are a derivative of the National Social Security System as regulated in Law Number 40 of 2004. However, this unemployment program has instead become a point of contention for stakeholders, particularly from the worker/labor group, who feel that the program does not provide benefits in terms of legal protection and fairness. Therefore, the researcher conducted a normative legal study on the principles of legal protection and justice contained in the articles of the regulation. This study uses a normative legal research method that is descriptively analytical. This research uses several approaches, namely: the statutory approach, the conceptual approach, and the comparative approach. (comparative approach). The focus of this research is to examine the principles of legal protection and the concept of justice in Government Regulation Number 37 of 2021. As a normative legal provision, this regulation needs to be reviewed again, evaluated, and supplemented with several articles or provisions that govern the implementation of the job loss guarantee program, so that it can uphold the principles of legal protection and justice, preventing this regulation from merely becoming an aspirational legal norm (ius constituendum) or a dead legal regulation/norm.